The Endoplasmic Reticulum Stress Sensor IRE1α in Intestinal Epithelial Cells Is Essential for Protecting against Colitis - Zhang, Hai-Sheng (J Biol Chem, 2015)
Intestinal epithelial cells (IECs) have critical roles in maintaining homeostasis of intestinal epithelium. Endoplasmic reticulum (ER) stress is implicated in intestinal epithelium homeostasis and inflammatory bowel disease; however, it remains elusive whether IRE1α, a major sensor of ER stress, is directly involved in these processes. We demonstrate here that genetic ablation of Ire1α in IECs leads to spontaneous colitis in mice. Deletion of IRE1α in IECs results in loss of goblet cells and failure of intestinal epithelial barrier function. IRE1α deficiency induces cell apoptosis through induction of CHOP, the pro-apoptotic protein, and sensitizes cells to lipopolysaccharide, an endotoxin from bacteria. IRE1α deficiency confers upon mice higher susceptibility to chemical-induced colitis. These results suggest that IRE1α functions to maintain the intestinal epithelial homeostasis and plays an important role in defending against inflammation bowel diseases.